Determination of lead, arsenic and nickel in commercial rice by flame atomic absorption spectroscopy with chemometrics for forensic comparison - Shamsha, Nur Sabrina (2022)
Rice, being an important food, is always associated with world food security. The presence of heavy metals in the commercial rice would poses potential health risks to the consumers, deserving determination and quantification. Furthermore, the elemental profiles of the rice could also aid in the sample-to-sample comparison. Therefore, this study was aimed to determine the contents of lead (Pb), arsenic (As), and nickel (Ni) in commercial rice by flame atomic absorption spectroscopy (FAAS) followed by the clustering and/or discrimination of rice samples through chemometrics. A total of 65 commercial rice samples were collected and physically examined. Subsequently, the samples were analysed using FAAS and decomposed by principal component analysis (PCA). The physical examination, including the shape and colour, allowed for the differentiation of rice samples between milled and glutinous rice, as well as white and colour rice, respectively. The elemental profiles, focusing on Pb, As, and Ni, were found different among the rice samples regardless of the rice groups. Up to 84% of the rice samples tested in this study were found to have contained Pb. Comparatively, the positive detection for the presence of As and Ni were in lower percentages, at 21% and 46% respectively under the experimental conditions. The elemental data was then logarithm transformed and statistically analysed by PCA, allowing for the formation of eight clusters. The samples in each cluster could be discriminated from the others, probably due to the differences in their respective elemental profiles. To conclude, the application of FAAS combined with the PCA in this study had successfully determined the presence of Pb, As, and Ni in certain rice samples, and subsequently grouped into respective clusters. The presence of such heavy metals in the commercial rice shall be given attention for further investigation to safeguard the food security, in addition to the forensic sample-to-sample comparison.